El hongo Erynia neoaphidis infectando el áfido Rhodobium porosum en Venezuela - Agudelo-Silva, F. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Erynia neoaphidis is identified as parasiting the aphid Rhodobium porosurn Sanderson (Homoptera: Aphididas) found in roses (Rosa sp.) in Venezuela The fungal structure found in dead bodies of aphids corresponded to primary conidias of 15 x 24u x 12 x 15u, x- = 22 x 12u, and secondary conidias of 13 x 21u x 12 x 15u, x-= 17x 13u in length- and withd respectively.